Business journalism ethics in Africa: a comparative study of newsrooms in South Africa, Kenya and Zimbabwe - Mare, Admire (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2010)
This study provides an insight into the state of business journalism ethics in Africa, firstly through an examination of newsroom ethical policies and secondly through an exploration of the way in which African business journalists negotiate ethical decision-making in their day-to-day news processing practices. Thirdly, it examines how the three African media organisations have responded in their newsroom policies and practices to the debates on the Africanisation of journalism ethics. In order to collect data, the researcher employed document analysis, semi-structured questionnaires and in-depth interviews. Three financial newspapers namely: Business Day in South Africa, Business Daily in Kenya and Financial Gazette in Zimbabwe were purposively chosen. In these African countries, business journalism has been steadily growing since the late 1960s, fuelled by the presence of robust stock exchanges, making the issue of business journalism ethics of central importance. Grounded in the sociology of news production paradigm, Bourdieu's journalistic field theory and debates on Africanisation of journalism ethics, this study identifies three major issues. First, the research found that while all three newspapers had clear ethical guidelines in place, and editors and journalists recognised the importance of ethical behaviour, ethical practice did not always follow. A disconnect exists between words (codes of ethics) and actions (practice) especially in Kenya and Zimbabwe, where business journalists are more susceptible to economic and political pressures. The argument is ethical considerations notwithstanding, people need to survive. This is largely due to the precarious economic basis of news organisations, lack of effective monitoring, and a pervasive culture of unethical behaviour at some sites. Second, the study also shows that institutional factors such as advertising, powerful news sources and interference from senior management make ethical business journalism difficult to practice. Third, Africanisation remains an academic issue with little movement towards that direction in most newsrooms studied. The findings of this study demonstrate that business editors in African newsrooms are confused on what 'Africanisation' entails especially given their shared view that journalism practices are universal. It recommends that business journalism codes of ethics informed by African values are long overdue. In terms of enforcement and monitoring of codes, it is important to use compliance officers or ombudsperson and periodically run in-house refresher courses on ethics and professionalism. It is imperative that the financial press improve the working conditions of its employees in order to lessen incidences of corruption which are threatening the credibility of media content and media organisation themselves.
Keywords: Journalism, Commercial; Journalistic ethics; Journalism, Commercial -- South Africa; Journalism, Commercial -- Kenya; Journalism, Commercial -- Zimbabwe; Business Day (South Africa); Business Daily (Kenya); Financial Gazette (Zimbabwe)